Women and Domestic Violence: Legal Protection Perspective - Arief, Hanafi (Pagaruyuang Law Journal, 2018)
This study aims to describe the position of women in the family/household, violence against women, as well as how the protection of laws against women victims of domestic violence. This research is the juridical normative and prescriptive. In a family, woman as the wife is a member of the family besides father and son. Women have the same position with the other family members, including equality in rights and opportunities as well as the protection of rights in the field of civil, political, economic, social, cultural, and other fields. Violence against women is a violation of the rights of women in the household. The birth of the Domestic Violence Act, Number 23, the year of 2004 was the protection of women, carried out based on the principles of respect for human rights, justice, gender equality and non discrimination. Protection is based with a variety of considerations, among them is that every citizen has the right to get a sense of security and freedom from all forms of violence.